Effectiveness of combined chain exercises on pain and function in patients with knee osteoarthritis - Olagbegi, Oladapo Michael; Adegoke, Babatunde Olusola Adeleke; Odole, Adesola C (Bangladesh Journal of Medical Science, 2016)
Objective: This randomized controlled trial was designed to investigate and compare the effectiveness of twelve-week open, closed and combined kinetic-chain exercises (OKCEs, CKCEs and CCEs) on pain and physical function (PF) in the management of knee osteoarthritis. Method: Ninety-six consecutive patients with knee OA were randomly assigned to one of OKCE, CKCE and CCE groups. Participants average daily pain (ADP), pain before and after walking (PBW and PAW), were evaluated using Visual Analogue Scale while PF was assessed using Ibadan Knee/Hip Osteoarthritis Outcome Measure. Results: Seventy-nine participants completed the study but data of another 4 participants who completed only 8-week treatment were included in data analysis (total=83; mean age = 61.10±13.75 years). The groups demographic and dependent variables were comparable at baseline but CCE group demonstrated significantly more reductions (p < 0.05) in ADP, PBW and PAW than OKCE and CKCE groups at weeks 4, 8 and 12 of the study. However, there were significant within group improvements (p < 0.05) in all four variables for the three groups. Conclusion: CCEs are better than OKCEs and CKCEs for pain reduction in though all three exercise regimens are singly effective. CCEs are recommended for improving treatment outcome for pain in patients with knee osteoarthritis. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.178-188